Tinjauan Hukum Penanaman Modal Asing di Sektor Perbankan dan Dampaknya Terhadap Kinerja Saham Perbankan di Pasar Modal (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This paper focuses on a legal review of foreign investment regulations in Indonesia, a crucial aspect that underpins most of the discussion. Furthermore, it frequently highlights the implications of legal regulations on investment, including foreign investment, in several related regulations, such as the Job Creation Law and the Investment Law, for market volatility, corporate governance, and stock prices in Indonesia. This paper emphasizes a normative-empirical context, focusing on a review of capital market investment regulations and secondary analyses conducted through several journals reporting on the effectiveness of foreign investment for local companies, enhancing their image as local companies, a trend inevitably driven by local interests. This is further supported by the use of various important theories, such as foreign investment theory, the legal framework for foreign investment, stock performance theory, and efficient investment, as crucial theoretical considerations in the discussion. The point of the results of the discussion in this writing is then emphasized on its focus, namely the results of the review of the legal regulations regarding capital markets that include foreign capital markets, which also discusses the results of research reports from various journals related to the implications of foreign investment regulations as well as the challenges and discussions of harmonization regarding existing investment regulations in Indonesia.